Pattern Synthesis With Closed-Form Array Response Control Algorithms - Shi, Xue (IEEE antennas and wireless propagation letters, 2022)
In this letter, the problem of array pattern synthesis is considered by developing two array response control algorithms. The devised two algorithms build on the basis of the accurate array response control approach, and both of them have closed-form solutions and low computational complexities. More specifically, the first proposed algorithm realizes multipoint array response control from an any given weight vector, and the second algorithm modifies the first one by avoiding the possible beam axis shift. The proposed two algorithms are able to control array responses accurately under the conditions of independence on steering vectors. By applying the first and the second array response control algorithm, two effective pattern synthesis methods for focused patterns and shaped patterns are devised, respectively. Representative examples are presented to demonstrate the performance of the proposed algorithms in array response control and pattern synthesis.